Service Function Chaining: Creating a Service Plane via Network Service Headers. - Quinn, Paul; Guichard, Jim (Computer (00189162), 2014)
As service chaining matures, interoperability is a must. Network service headers provide the required data-plane information needed to construct topologically independent service paths as well as to pass opaque metadata between classification and service functions.